Pengaruh Model Pembelajaran Flipped Classroom Terhadap Hasil Belajar Siswa pada Mata Pelajaran Sosiologi Kelas X SMAN 1 Enam Lingkung (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to determine the influence of the flipped classroom model on student learning outcomes in Sociology class X at SMA Negeri 1 Enam Lingkung. This study is a quantitative research using a quasi-experimental approach. The population of this study is the 10th-grade students of SMA Negeri 1 Enam Lingkung. The sample consists of class XE.6 as the experimental class and XE.7 as the control class, each comprising 36 students. Data collection techniques use objective tests with 40 questions, and the obtained data are analyzed using the t-test. The results show that the average score of the experimental class is 76,38, while the average score of the control class is 65,13. Based on the t-test calculation, the t-count value is greater than the t-table value, which is 4.250 > 1.994, indicating a significant difference in learning outcomes at a significance level of α = 0.05. Therefore, it can be concluded that the use of the flipped classroom learning model has a significant effect on student learning outcomes in the Sociology subject for 10th-grade students at SMA Negeri 1 Enam Lingkung